NEW CHALLENGES FACING RETAIL AND MARKETING – SUSTAINABLE CONSUMPTION AND INNOVATIONS OF TRADE ENTERPRISES - Magdalena Stefańska; Grażyna Śmigielska (Polityki Europejskie, Finanse i Marketing)
Sustainable consumption is a term related to the type of consumer behavior being a part of the broader concept of sustainable development. In the process of selecting the method of satisfying their needs, consumers take into account a number of factors which minimize the negative influence of their buying decisions on the natural environment and the society. The goal of the article is to identify consumers aiming at sustainable consumption and to explain the way in which companies respond to these consumers’ needs by means of innovations – particularly that of the marketing and organizational nature. The study focuses on retail companies for a few reasons. First of all, companies of this type have the following characteristics: proximity to consumers, cooperation with producers in creating their offer, as well as shaping sales channels and developing a variety of time and space solutions facilitating the efficient need satisfaction. What is more, they are also leaders in innovation – these are the retail companies that adopted a number of innovations during the economic transformation period. In the last part of the article the companies’ objectives are confronted with the consumers’ aims, as well as barriers to development and factors conducive to sustainable consumption are discussed.